Determination of Distribution Center Location using Analysis of Time-Based Set Covering Model and Maximal Covering Model Analysis - Rainisa Maini Heryanto; Santoso Santoso (OPSI, 2023)
The distribution or delivery process is one factor that affect customer satisfaction as the goal of supply chain. In order for supply chain to be competitive in competition, delivery time is an important factor to manage, so that it could provide high service level value. One factor that could affects distribution or delivery is distribution center location. A strategic distribution center location would facilitate and speed up distribution process. This research discusses model for determining location of distribution center so that delivery could be made at the right amount and in the right time by analyzing of time-based using set covering model and maximal covering model. The numerical example in this research is case study on paint supply chain in Bandung which has a number of delivering clusters. Each cluster consists of a number of building material stores which are located scattered. There is one cluster that has problems in fulfilling demands and delivery times. The analysis made could be used to determine the distribution center location so that it could serve all consumer demands. Based on the calculation results, it was found that there were two distribution center locations. Two distribution centers could fulfill the objective function of cost minimization and satisfy all demands. The results of the sensitivity analysis show that there are several factors that influence the determination of location number.